Genome-wide association study identifies four loci associated with eruption of permanent teeth. - Frank Geller (Public Library of Science (PLoS), 2011)
The sequence and timing of permanent tooth eruption is thought to be highly heritable and can have important implications for the risk of malocclusion, crowding, and periodontal disease. We conducted a genome-wide association study of number of permanent teeth erupted between age 6 and 14 years, analyzed as age-adjusted standard deviation score averaged over multiple time points, based on childhood records for 5,104 women from the Danish National Birth Cohort. Four loci showed association at P<5×10(-8) and were replicated in four independent study groups from the United States and Denmark with a total of 3,762 individuals; all combined P-values were below 10(-11). Two loci agreed with previous findings in primary tooth eruption and were also known to influence height and breast cancer, respectively. The two other loci pointed to genomic regions without any previous significant genome-wide association study results. The intronic SNP rs7924176 in ADK could be linked to gene expression in monocytes. The combined effect of the four genetic variants was most pronounced between age 10 and 12 years, where children with 6 to 8 delayed tooth eruption alleles had on average 3.5 (95% confidence interval: 2.9-4.1) fewer permanent teeth than children with 0 or 1 of these alleles.